1994
DOI: 10.1007/bf01029514
|View full text |Cite
|
Sign up to set email alerts
|

Asset specificity and vertical integration in franchising

Abstract: Asset specificity, franchising, vertical integration,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 13 publications
1
50
0
4
Order By: Relevance
“…Bercovitz (1999), Brickley et al (1991), Minkler (1990), Brickley and Dark (1987) and Norton (1988) have confirmed that the franchise rate increases with various proxys of geographical distance between the corporate center and the sales units (distance is used here to indicate higher costs of controlling corporate units). Minkler and Park (1994) also find that the proportion of franchised units is inversely proportional to the value of the trademarks owned by the franchisor (measured through the ratio of stock market and book values of the firm). Finally, Brickley and Dark (1987) also note that the franchise rate is lower in industries characterized by non-repeat purchases, but later works have presented more ambiguous results (Brickley et al, 1991;Lafontaine, 1995).…”
Section: Controlling the Behavior Of The Corporate Units And Of The Fmentioning
confidence: 97%
“…Bercovitz (1999), Brickley et al (1991), Minkler (1990), Brickley and Dark (1987) and Norton (1988) have confirmed that the franchise rate increases with various proxys of geographical distance between the corporate center and the sales units (distance is used here to indicate higher costs of controlling corporate units). Minkler and Park (1994) also find that the proportion of franchised units is inversely proportional to the value of the trademarks owned by the franchisor (measured through the ratio of stock market and book values of the firm). Finally, Brickley and Dark (1987) also note that the franchise rate is lower in industries characterized by non-repeat purchases, but later works have presented more ambiguous results (Brickley et al, 1991;Lafontaine, 1995).…”
Section: Controlling the Behavior Of The Corporate Units And Of The Fmentioning
confidence: 97%
“…Maturity in an entrepreneurial venture favors the attraction of resource providers, particularly in franchising (Carney and Gedajlovic, 1991;Minkler and Park, 1994;Combs and Ketchen, 2003;Castrogiovanni et al, 2006a) because it reveals information about the franchisor's experience, knowledge and past success to potential investors. On the one hand, franchisor maturity suggests that the business concept has been successful in different locations and over several years and that the franchisor has probably learnt to manage franchisees effectively (Bradach, 1997), developing abilities in control and contractual design.…”
Section: Franchise Package Appeal: Maturity and Initial Investmentmentioning
confidence: 99%
“…Segundo os autores do primeiro grupo, a explicação para o emprego das formas plurais está alinhada ao modelo de Williamson (1991) ao apontar que a existência das diferentes estruturas de governança advém do fato das transações serem distintas em pelo menos um atributo (MINKLER e PARK, 1994). O modelo teórico proposto por Menard (2013) adicionou os atributos ambiguidade, que surge em virtude da dificuldade para analisar a especificidade dos ativos no momento de realizar as transações, e complexidade das transações na análise da adoção de formas plurais.…”
Section: Formas Plurais De Governançaunclassified